Experimental study on a photovoltaic panel using an active water cooling method - Zulkefle, Ahmad Aizan; Halimi, Ahmad Suhaib; Zainon, Maslan; Zulkefle, Azman; N. Saleh (Research and Scientific Innovation Society, 2025)
Photovoltaic (PV) electric power generation is a promising technology for harvesting energy from the sun. However, it is difficult to obtain consistent and efficient energy from solar panels, which results in fluctuations in the battery’s state of charge (SOC). This condition may cause overcharging or undercharging, both of which can reduce the battery’s lifespan. Additionally, variations in solar irradiance, particularly changes in sunlight intensity, affect the efficiency of the solar panel and, consequently, the battery SOC. A major issue with solar panels arises when their temperature increases, as higher temperatures reduce their efficiency. This reduction in solar photovoltaic efficiency occurs under increasing and unstable environmental temperatures. To ensure the sustainability and improved performance of solar photovoltaic systems, this project proposes the development of an active water-cooling system using Arduino. This system is intended to help users enhance the efficiency of solar panels. This paper analyzes the effect of an active water-cooling system on the efficiency of a solar panel. The outcomes of this research align with SDG 7, SDG 9, SDG 12, and SDG 13 by enhancing photovoltaic efficiency through an active water-cooling method, thereby supporting clean energy, technological innovation, resource-efficient production, and climate action.